Evaluation of the Sustainability of the Slum Settlement Management Program in Tegal Sari Mandala Village II: Ecological and Social Perspective - Nur Ratih Kuntari; Abdi Sugiarto; Cut Nuraini (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
Slums are one of the biggest challenges in sustainable urban development. In the midst of the government's efforts to run a program to handle slum organizations, the issue of miscarriage after physical intervention often goes unnoticed. This study aims to stop the slum management program in Tegal Sari Mandala II Village, with a Mixed Methods approach that combines linear multiple quantitative regression analysis and a qualitative descriptive approach.The results show that community participation has a significant effect on poverty programs, while infra-structure quality has not shown a statistically strong relationship. Qualitative findings support these results, where residents feel more attached to the programs they have followed in the past. Meanwhile, a number of infrastructures that are not in accordance with needs are considered less effective in supporting sustainability. This study concludes that the desire of the program is not only determined by technical aspects, but also by social, institutional, and cultural factors that are intertwined. Strategic recommendations include strengthening participation, improving design based on local needs, and integration with spatial policies.